Diversity and molecular characterization of Insect - specific Flavivirus in mosquitoes (Diptera: Culicidae) collected in Central and Northern Argentina - Farias, Adrian Alejandro (2022)
In order to study the diversity and phylogenetic relationships among insect-speci c aviviruses circulating in the central and northern regions of Argentina we performed molecular detection and characterization of the NS5 protein gene in mosquitoes collected in Córdoba, Chaco and Tucumán provinces between 2001 and 2012, Sixty eight out of 1776 pools were positive. The KRV, CFA and CxFV viruses were detected by the generic PCR method, achieving the analysis of the existing phylogenetic relationships in the Flavivirus genus and the characterization of circulating CxFV in Argentina. It has also been possible to detect, for the rst time, the CxFV virus in the mosquito species Haemagogus spegazzini.